Assessing the Welfare Effects of Unemployment Benefits Using the Regression Kink Design - Camille Landais (Institute for the Study of Labor (IZA), 2013)
I investigate in this paper partial equilibrium labor supply responses to unemployment insurance (UI) in the US. I use administrative data on the universe of unemployment spells in five states from the late 1970s to 1984, and non-parametrically identify the effect of both benefit level and potential duration in the regression kink (RK) design using kinks in the schedule of UI benefits. I provide many tests for the robustness of the RK design, and demonstrate its validity to overcome the traditional issue of endogeneity in UI benefit variations on US data. I also show how, in the tradition of the dynamic labor supply literature, one can identify the purely distortionary effects of UI using variations along the returns-to-employment profile brought about by exogenous variations in the benefit level as well as in the benefit duration. I then use these estimates to calibrate the welfare effects of an increase in UI benefit level and in UI potential duration.
Keywords: J22; 330; unemployment insurance; regression kink design